European Union’s Development Assistance and Nation Building: A Case of Mogadishu, Somalia - Hassan, Abdulkadir Mohamed; Hassan, Abdikarim Sheikh Mohamed (Multidisciplinary Journal of Horseed International University (MJHIU), 2025)
This study examines the European Union's (EU) contributions to nation-building in Mogadishu, Somalia, focusing on three key areas: institutional consolidation, state stabilization, and sustainable development. The purpose of the study is to analyze how the EU’s interventions have influenced the nation-building process in Somalia’s capital. A qualitative research methodology was employed, using case studies, document reviews, and in-depth interviews with policymakers, EU officials, and local stakeholders. The findings reveal that the EU’s sustainable development initiatives have significantly enhanced economic growth and social infrastructure, contributing to improved living standards in Mogadishu. The EU’s state stabilization efforts, particularly in security sector reforms, have played a pivotal role in reducing violence and strengthening local governance. Furthermore, the EU’s institutional consolidation initiatives have fostered more transparent and accountable governance structures, contributing to the overall stability and functionality of Somalia’s public institutions. In conclusion, the study finds that the EU’s multifaceted approach to nation-building in Mogadishu has yielded positive outcomes, though challenges remain in ensuring the long-term sustainability of these efforts. The study recommends continued support for capacity building and the enhancement of local governance mechanisms to ensure lasting peace and development. This research contributes to the knowledge of international development and governance by providing insights into the role of external actors like the EU in fragile states.